Traditional craftsmanship: the origin, culture, and challenges of batik industry in Malaysia - Mohamad Akhir, Noor Haslina; Ismail, Normaz Wana; Said, Rusmawati; Kaliappan, Shivee Ranjanee (Springer, 2015)
Batik is a process of dyeing fabric by making use of a resist technique. Approximately, 70 % of the national industry in Malaysia is derived from SMEs,and microenterprise is one of the main components in SMEs. In the Malaysian context, most of batik enterprises have been categorized in SME industries.Recently, United Nations Conference on Trade and Development (UNCTAD).had classified the craft industry as one of the items in the creative industries.They believe the creative industries will provide new opportunities for developing countries to leapfrog into emerging high-income countries due to the contribution on output level, employment, and tourism sector. Even though batik production has long been established in this country, unfortunately, it is still dominated by microenterprises with around 86 %. Hence, this paper is written to bring readers to understand the origin, culture, and the challenges faced by batik makers in order to preserve and flourish batik industry in Malaysia.